Results of a Phase 1/2a dose–escalation study of FF-10501-01, an IMPDH inhibitor, in patients with acute myeloid leukemia or myelodysplastic syndromes. Issue 8 (2nd July 2020) - Garcia-Manero, Guillermo; Pemmaraju, Naveen; Alvarado, Yesid; Naqvi, Kiran; Ravandi, Farhad; Jabbour, Elias; De Lumpa, Ricardo; Kantarjian, Hagop; Advani, Anjali; Mukherjee, Sudipto; Gerds, Aaron; Carraway, Hetty E.; et al.
Abstract: FF-10501-01 potently inhibits inosine-5-monophosphate dehydrogenase (IMPDH), inducing anti-proliferative and pro-apoptotic effects in acute myeloid leukemia (AML) human cell lines resistant to hypomethylating agents. In this Phase 1/2a study, Phase 1 enrolled 38 patients with relapsed/refractory AML ( n  = 28) or myelodysplastic syndromes (MDS/CMML, n  = 10) to receive FF-10501 oral doses 50–500 mg/m 2 BID for 14 or 21 days out of each 28-day cycle. Fifteen additional patients with HMA-resistant MDS/CMML (Phase 2a) were treated at 400 mg/m 2 BID for 21 days. Most Phase 1 adverse events were disease-related and low-grade. 3 of 19 (16%) evaluable AML patients achieved partial remission (31, 7, and 5 months). 2 of 20 (10%) evaluable MDS/CMML patients (Phase 1 and 2a) attained marrow complete remission, one continuing treatment for 17 months. While FF-10501-01 demonstrated clinical activity and target inhibition in heavily pretreated patients with AML and MDS/CMML, increased mucositis events led to Phase 2a closure (ClinTrials.gov#NCT02193958).